Висвітлення «режиму санації» в Польщі 1926–1939 рр. у шкільних підручниках з історії - Bakhanova, Svetlana; Баханова, Світлана (Східноєвропейський національний університет ім. Лесі Українки, 2013)
У статті на основі аналізу шкільних підручників із новітньої історії простежено еволюцію оцінок «режиму санації» в Польщі 1926–1939 рр. від диктаторського режиму до авторитарного; парламентаризму, спрямо-ваного на консолідацію нації; авторитарного режиму з деякими ознаками тоталітаризму.Processes of the reforming of different spheres of Ukrainian life motivate to study the historical experience of conversion. At the same time singularity of modern historiographical situation suggests to attract new historiographical sources, in particular, school textbooks, the main requirement for which is scientificity suggesting the orientation of the content on new facts and modern interpretation. The «regime of sanation» was the subject of historical researchers which did not consider the aspect of its lighting in school textbooks.
Lighting the «Regime of Sanation» in School History Textbooks
Keywords: «режим санації»; Ю. Пілсудський; шкільний підручник; Poland; «regime of sanation»; Y. Pilsudsky; school textbook; Польща